Experiences of Cardiovascular Surgery Intensive Care Nurses in the Care of Patients With Postoperative Cognitive Dysfunction: A Qualitative Study - Hatice Azizoğlu PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Postoperative cognitive dysfunction (POCD) is the development of cognitive decline following anesthesia and surgery. The incidence of POCD is more pronounced in patients undergoing cardiac surgery than in patients undergoing non-cardiac surgery. This study aims to evaluate the experiences, knowledge status, and clinical practice interventions of nurses caring for patients diagnosed with POCD. Ten nurses working in the intensive care unit of cardiovascular surgery participated in this study, which used a phenomenological design, one of the qualitative research types. We collected the data face-to-face between January and March 2023 using the individual in-depth interview method. The data were analyzed by the researcher using thematic analysis. The study identified 13 main themes: cognitive, behavioral, emotional problems, occupational difficulties, increasing duration, age, premorbid period, psychological resilience, effective coping skills, interaction, restraint, external support systems, and cognitive structuring. After cardiovascular surgery, patients should be evaluated not only for cardiac but also for cognitive, emotional, and behavioral factors. In addition, the risk factors that cause POCD, the difficulties faced by nurses, and their coping skills are the effects that shape the patient care process of POCD.